TIPOLOGI ARSITEKTUR RUMAH SABU (AMMU HAWU), SEBUAH PENDEKATAN DESKRIPTIF ANTROPOLOGIS - Jeraman, Pilipus (Universitas Atma Jaya Yogyakarta, 2019)
Abstract: The architecture of the house of Sabu (ammu hawu) is one of the riches of vernacular architecture that still exists in East Nusa Tenggara and is well preserved by the ethnic Sabu community, which inhabits the islands of Sabu and Raijua Island. This research provides a descriptive description of the typological characteristics of Sabu's house architecture (ammu hawu) and its settlement environment. The typology study on Sabu house (ammu hawu) was developed with a descriptive anthropological approach. The results showed that the architecture of the house of Sabu (ammu hawu) has distinctive characteristics that are in harmony with the cultural background of the Sabu community. Based on the typology of functions and forms known to the typology of houses on Sabu island there are three typologies, namely ammu hawu (roukoko), ammu atta, and ammu jawa.Keywords: typology, ammu hawu, descriptive, anthropologicalAbstrak: Arsitektur rumah Sabu (ammu hawu) adalah salah satu kekayaan arsitektur vernakular yang masih eksis di Nusa Tenggara Timur dan terpelihara dengan baik oleh masyarakat etnis Sabu, yang mendiami Pulau Sabu maupun Pulau Raijua. Penelitian ini memberi gambaran deskriptif tentang karakteristik tipologi arsitektur rumah Sabu (ammu hawu) dan lingkungan permukimannya. Kajian tipologi terhadap rumah Sabu (ammu hawu)Â ini dikembangkan dengan pendekatan deskriptif antropologis. Hasil penelitian menunjukkan, arsitektur rumah Sabu (ammu hawu) memiliki karakteristik khas yang selaras dengan latar belakang kebudayaan masyarakat Sabu. Berdasarkan tipologi fungsi dan bentuk diketahui tipologi rumah di pulau Sabu ada tiga tipologi, yakni ammu hawu (roukoko), ammu atta, dan ammu jawa.Â Â Kata kunci: tipologi, ammu hawu, deskriptif, antropologis.